HKS Misinfo Review 2020
DOI: 10.37016/mr-2020-42
|View full text |Cite
|
Sign up to set email alerts
|

The Twitter origins and evolution of the COVID-19 “plandemic” conspiracy theory

Abstract: Tweets about “plandemic” (e.g., #plandemic) – the notion that the COVID-19 pandemic was planned or fraudulent – helped to spread several distinct conspiracy theories related to COVID-19. But the term’s catchy nature attracted attention from anti-vaccine activist filmmakers who ultimately created Plandemic the 26-minute documentary. Plandemic falsely attacks NIAID Director Dr. Anthony Fauci, among others, and an eventual coronavirus vaccine. The film, which has since been widely discredited, appeared to at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 21 publications
3
40
0
2
Order By: Relevance
“…However, our findings suggest that these efforts did not remove the influence of the three theories on which we focused. This finding is consistent with evidence from a study conducted in April 2020 that found considerable evidence of tweeted comments supporting a conspiracy theory about the pandemic [ 68 ] and other work suggesting that conspiracy claims that are interdicted quickly reappear elsewhere [ 17 , 45 ]. Although experience in China suggests that rapid refutation of pandemic rumors can be successful in reducing transmission of misinformation on social media [ 69 ], the expanse, variety, and decentralized nature of US media make such efforts more challenging than in countries whose media are largely government controlled.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our findings suggest that these efforts did not remove the influence of the three theories on which we focused. This finding is consistent with evidence from a study conducted in April 2020 that found considerable evidence of tweeted comments supporting a conspiracy theory about the pandemic [ 68 ] and other work suggesting that conspiracy claims that are interdicted quickly reappear elsewhere [ 17 , 45 ]. Although experience in China suggests that rapid refutation of pandemic rumors can be successful in reducing transmission of misinformation on social media [ 69 ], the expanse, variety, and decentralized nature of US media make such efforts more challenging than in countries whose media are largely government controlled.…”
Section: Discussionsupporting
confidence: 90%
“…A notable characteristic of conspiracy beliefs is the tendency for belief in any one to be associated with acceptance of others [ 2 , 15 - 17 ]. In the United States, three such beliefs prevalent early in the pandemic [ 1 , 2 , 4 ] concerned suspicions that the pandemic was the result of malign actions by either the Chinese government or the pharmaceutical industry or that some in the US government were exaggerating the danger of COVID-19 to undermine the president of the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has highlighted an association between conservative political leaning and misinformation sharing (Grinberg et al, 2019) and exposure (Chen et al, 2020). The proliferation of conspiratorial narratives about COVID-19 (Kearney et al, 2020;Evanega et al, 2020) and voter fraud (Benkler et al, 2020) in the run-up to the 2020 U.S. election is consistent with this association. As social media platforms have moved to more aggressively moderate disinformation around the election, they have come under heavy accusations of political censorship.…”
Section: Discussionsupporting
confidence: 58%
“…The COVID-19 pandemic has been accompanied by a deluge of complex and changing information, resulting in an “infodemic”—an overabundance of information rife with misinformation and hoaxes [ 1 , 2 , 3 ]. Online communication channels are especially vulnerable to the spread of incorrect information, and many social media news feeds are refreshed automatically with similarly misleading content [ 1 , 2 ]. However, online communication channels have also been a central resource for reliable health information throughout the pandemic.…”
Section: Introductionmentioning
confidence: 99%